A review on natural fiber reinforced composites. (2020) - Kerni, Love; Singh, Sarbjeet; Patnaik, Amar; Kumar, Narinder
Abstract: Materials plays important role for survival of any manufacturing industry. Composite materials replace the conventional materials because of their high specific strength, strong damping capacity and high specific modulus. In modern era, natural fiber reinforced polymer composites came into light because of promising properties of natural fibers such as light weight, water resistance, high impact strength, environment friendly etc. In this study, different types of natural fibers that can be used as reinforcement in polymer composite are discussed. Various methods of production and steps involved in processing of natural fiber reinforced composite are presented. Then, mechanical and tribological properties of these composites are reviewed and presented. The different applications of natural fiber reinforced polymer composite are also discussed.